1998
DOI: 10.1017/s1062798700003227
|View full text |Cite
|
Sign up to set email alerts
|

The new challengers: greens and right-wing populist parties in western Europe

Abstract: The decline in confidence in the traditional parties in Western Europe has manifested itself through the emergence of the Green parties on the Left and populist parties on the Right. Despite successes in some countries, these parties have remained small, although they have been able, respectively, to play on the growth of ‘post-materialist’ values on the Left, and of anti-immigrant sentiments on the Right. The prospects for these parties are not very good, in particular for the right-wing populist parties, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 1 publication
(1 reference statement)
0
20
0
1
Order By: Relevance
“…The so-called challenger parties are a particularly relevant party category because they are often perceived as a threat to the party establishment (Meguid, 2005) and assumed to use populist communication to generate attention (Kriesi, 2014). Throughout the various crisis cycles since the 1980s, new challenger parties from both the left and the right have emerged and gained success in many Western democracies (Hobolt & Tilley, 2016;Müller-Rommel, 1998). Kriesi (2014) argues that these new challenger parties may be perceived as a threat to the establishment because they highlight problems that have been neglected by mainstream parties, mobilize outside of the electoral channels, and resort to creative, innovative forms of protest communication.…”
Section: Research Questions and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The so-called challenger parties are a particularly relevant party category because they are often perceived as a threat to the party establishment (Meguid, 2005) and assumed to use populist communication to generate attention (Kriesi, 2014). Throughout the various crisis cycles since the 1980s, new challenger parties from both the left and the right have emerged and gained success in many Western democracies (Hobolt & Tilley, 2016;Müller-Rommel, 1998). Kriesi (2014) argues that these new challenger parties may be perceived as a threat to the establishment because they highlight problems that have been neglected by mainstream parties, mobilize outside of the electoral channels, and resort to creative, innovative forms of protest communication.…”
Section: Research Questions and Hypothesesmentioning
confidence: 99%
“…We also recorded the age of each party. Since most challenger parties emerged in recent decades (Hobolt & Tilley, 2016;Müller-Rommel, 1998;Weber, 2017), we coded all parties founded after 1980 as challenger parties. Furthermore, two dummies for Facebook and Twitter (vs. political talk shows) were calculated.…”
Section: Operationalizationmentioning
confidence: 99%
“…15 What is more relevant for the purposes of this present discussion, however, is that it has also probably helped to create the space for the emergence of so-called anti-party parties, both of the right and of the left -the so-called 'challenger parties' which seek to mobilise populist anti-establishment feelings and to reflect or even exploit the growing sense of distance from politics. 16 Such assaults on the world of the parties are clearly much more feasible when that world is seen to be both separate and self-enclosed, and this is clearly more likely to be the case in those polities characterised by a coalescent elite culture. 17 Indeed, it is now more than 30 years ago that Robert Dahl 18 first suggested that this style of politics, which was already emerging in nuce in the early 1960s, might actually provoke conflict, since it is a politics which would be seen as 'too remote and bureaucratised, too addicted to bargaining and compromise, [and] too much an instrument of political elites and technicians'.…”
Section: The Green Challenge and Political Competitionmentioning
confidence: 99%
“…Populism can be found in parties, movements or leaders with different core ideologies: right-wing parties (see among a vast literature, Taggart, 1995;Mudde, 2007) left-wing parties (Stavrakakis and Katsambekis, 2014;Weyland, 2013;Roodujin and Akkerman, 2015) and even liberals and greens (Zaslove, 2008;Müller-Rommel, 1998).…”
Section: Toward a Minimal Definitionmentioning
confidence: 99%